
I'm assuming you mean the rule described in http://en.wikibooks.org/wiki/Formal_Logic/Sentential_Logic/Inference_Rules
type Disj a b = Either a b
disj_elim :: Disj a b -> (a -> c) -> (b -> c) -> c disj_elim (Left a) a2c b2c = a2c a disj_elim (Right b) a2c b2c = b2c b
If you know "either a is true, or b is true"
and you know "from a, I can prove c",
and you know "from b, I can prove c",
then you can prove c.
-- ryan
On 2/8/08, PR Stanley
Hi folks The disjunction elimination rule: I've been trying to make sense of it and I think I have had some success; however, it's far from adequate. I wonder, is there a way of demonstrating it in Haskell? A code frag with a jargon-free explanation would be mucho appreciated. Cheers, Paul
_______________________________________________ Haskell-Cafe mailing list Haskell-Cafe@haskell.org http://www.haskell.org/mailman/listinfo/haskell-cafe